Solution X-ray scattering studies on the dengue virus non-structural protein 5 and -3 as well as the capsid protein - Saw, Wuan Geok (2017)
Dengue virus (DENV), which is the causative agent of dengue, is a single positive-stranded RNA virus. The structural information of two DENV non-structural proteins, NS5 and NS3, which play a central role in the genome replication, were gathered using small-angle X-ray scattering (SAXS). SAXS revealed that NS5 from all four serotypes adopt an extended and a slightly flexible conformation in solution, with DENV-4 NS5 being slightly more compact and less flexible than the other three serotypes. Three linker residues, S266, T267 and K271 were identified as the key residues responsible for this compactness. Upon adding RNA into the NS5 solution, an increase in size of NS5 was detected using SAXS. Furthermore, the solution data of DENV-4 NS2B18NS3 discloses a favorable domain-domain arrangement, which allows the binding of ADP-Mn2+ by the helicase. In addition, the unassigned N-terminal residues of the DENV-2 capsid protein were analyzed using SAXS, and revealed a highly flexible and extended conformation in solution.